The Influence of Ethical Orientation and Types of University on Students' Perceptions of Creative Accounting - Agus Putranto; M. Trihudiyatmanto (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2022)
Purpose - The purpose of this study was to identify the effect of professional accountant ethics, ethical orientation, level of accounting knowledge, type of university on creative accounting (a case study on economics students, al-Quran science university, Central Java in Wonosobo. The data used in this study was by sharing questionnaire directly to Accounting students, Faculty of Economics, Al Quran Science University, Central Java. Methodology- The population of this research is economics students class 2021, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo. The analytical method used in this study is multiple linear regression analysis, then using descriptive statistical tests, validity tests, reliability tests, goodness of fit tests, normality tests, multicollinearity tests, heteroscedasticity tests, and hypothesis testing including the coefficient of determination test and the significant test of the regression coefficient with 5% significance level. Results - The results of this study indicate that ethical orientation and type of university have a positive effect on creative accounting